Psychosocial Well-being of Working Mothers in Sivaganga District of Tamil Nadu - S. , Geetha; K. , Manimekalai; I. , Sivakumar (International Journal of Psychosocial Rehabilitation, 2020)
Women’s roles are emerging differently with new commitment and career oriented as well as a commitment to families. So, this, in turn, leads to a number of stress and strain among working mothers. While working parallel to men at the workplace, working mothers also play multiple roles such as child rears, parents, teachers, caretakers of their elderly parents, and many more, which become very much strenuous for them. It is the added responsibility and burden of chores that add to daily hassles or stress for them, especially in working mothers with young children and usage of social network account which definitely affect their psychological well-being.